Synthesis and Quantitative Structure-Property Relationships of Side Chain-Modified Hyodeoxycholic Acid Derivatives - Antimo Gioiello; Antonio Macchiarulo; Roberto Pellicciari; Roberto Nuti; Roccaldo Sardella; Benedetto Natalini; Paola Sabbatini; Paolo Filipponi (Molecules, 2013)
Bile acids have emerged as versatile signalling compounds of a complex network of nuclear and membrane receptors regulating various endocrine and paracrine functions. The elucidation of the interconnection between the biological pathways under the bile acid control and manifestations of hepatic and metabolic diseases have extended the scope of this class of steroids for in vivo investigations. In this framework, the design and synthesis of novel biliary derivatives able to modulate a specific receptor requires a deep understanding of both structure-activity and structure-property relationships of bile acids. In this paper, we report the preparation and the critical micellization concentration evaluation of a series of hyodeoxycholic acid derivatives characterized by a diverse side chain length and by the presence of a methyl group at the alpha position with respect to the terminal carboxylic acid moiety. The data collected are instrumental to extend on a quantitative basis, the knowledge of the current structure-property relationships of bile acids and will be fruitful, in combination with models of receptor activity, to design and prioritize the synthesis of novel pharmacokinetically suitable ligands useful in the validation of bile acid-responsive receptors as therapeutic targets.